Sustainable and Robust Graphene Cellulose Paper Decorated with Lithiophilic Au Nanoparticles to Enable Dendrite‐free and High‐Power Lithium Metal Anode. Issue 31 (14th May 2021) - Diao, Wan‐Yue; Xie, Dan; Li, Yan‐Fei; Jiang, Ru; Tao, Fang‐Yu; Sun, Hai‐Zhu; Wu, Xing‐Long; Zhang, Xiao‐Ying; Zhang, Jing‐Ping
Abstract: Lithium metal anodes (LMAs) with high energy density have recently captured increasing attention for development of next‐generation batteries. However, practical viability of LMAs is hindered by the uncontrolled Li dendrite growth and infinite dimension change. Even though constructing 3D conductive skeleton has been regarded as a reliable strategy to prepare stable and low volume stress LMAs, engineering the renewable and lithiophilic conductive scaffold is still a challenge. Herein, a robust conductive scaffold derived from renewable cellulose paper, which is coated with reduced graphene oxide and decorated with lithiophilic Au nanoparticles, is engineered for LMAs. The graphene cellulose fibres with high surface area can reduce the local current density, while the well‐dispersed Au nanoparticles can serve as lithiophilic nanoseeds to lower the nucleation overpotential of Li plating. The coupled relationship can guarantee uniform Li nucleation and unique spherical Li growth into 3D carbon matrix. Moreover, the natural cellulose paper possesses outstanding mechanical strength to tolerate the volume stress. In virtue of the modulated deposition behaviour and near‐zero volume change, the hybrid LMAs can achieve reversible Li plating/stripping even at an ultrahigh current density of 10 mA cm −2 as evidenced by high Coulombic efficiency (97.2 % after 60 cycles) and ultralong lifespan (1000 cycles) together with ultralow overpotential (25 mV). Therefore, this strategy sheds light on a scalable approach to multiscale design versatile Li host, promising highly stable Li metal batteries to be feasible and practical. Abstract : Sustainable graphene cellulose paper decorated with lithiophilic Au nanoparticles provides abundant nucleation sites and guarantees uniform Li deposition. And the large specific surface area of cellulose paper lowers local current density and avoids concentration polarization near the surface of electrode. Meanwhile, cellulose paper scaffold with good mechanical strength substantially alleviates the volume expansion of metal Li. Benefited from the synergy between Au nanoparticles and cellulose paper, the electrochemical performance of the Au−GCP electrode is significantly improved even at high current density.